2012
DOI: 10.1042/an20120058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Grey Matter in Thalamus and Basal Ganglia Based on EEG α3/α2 Frequency Ratio Reveals Specific Changes in Subjects with Mild Cognitive Impairment

Abstract: GM (grey matter) changes of thalamus and basal ganglia have been demonstrated to be involved in AD (Alzheimer's disease). Moreover, the increase of a specific EEG (electroencephalogram) marker, α3/α2, have been associated with AD-converters subjects with MCI (mild cognitive impairment). To study the association of prognostic EEG markers with specific GM changes of thalamus and basal ganglia in subjects with MCI to detect biomarkers (morpho-physiological) early predictive of AD and non-AD dementia. Seventy-four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Complex patterns involving subcortical networks have been described by Moretti et al in the setting of memory impairment and dementias. 39 This type of quantitative analysis may provide a fundamentally different observation than the current qualitative assessment as presented here.…”
Section: Discussionmentioning
confidence: 84%
“…Complex patterns involving subcortical networks have been described by Moretti et al in the setting of memory impairment and dementias. 39 This type of quantitative analysis may provide a fundamentally different observation than the current qualitative assessment as presented here.…”
Section: Discussionmentioning
confidence: 84%
“…Interconnected with prefrontal cortical structures, the caudate nucleus has been implicated in a wide range of cognitive functions (Haber, 2016; Zhang, et al, 2012). Studies have also reported volumetric changes of the caudate in neurological and psychiatric conditions, including mild cognitive impairment (Moretti, et al, 2012) and Alzheimer’s disease (Jiji, et al, 2013; Yang, et al, 2012), but the literature of healthy aging is limited. An earlier study reported volumetric reduction of the right caudate in relation to association memory deficits in older healthy adults (Bauer, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interconnected with prefrontal cortical structures, the caudate nucleus has been implicated in a wide range of cognitive functions (Haber, 2016;Zhang, Ide, & Li, 2012). Studies have also reported volumetric changes of the caudate in neurological and psychiatric conditions, including mild cognitive impairment (Moretti, Paternico, Binetti, Zanetti, & Frisoni, 2012) and…”
Section: Gray Matter Volumetric Reduction In Association With Agingmentioning
confidence: 99%
“…The fimbria was included in the hippocampal body, while the grey matter rostral to the fimbria was excluded. The hippocampal tail was traced until it was visible as an oval shape located caudally and medially to the trigone of the lateral ventricles [54] [55]. The intraclass correlation coefficients were 0.95 for the hippocampus and 0.83 for the amygdala.…”
Section: Mri Scans and Amygdalo-hippocampal Atrophy Evaluationmentioning
confidence: 99%